2011
DOI: 10.2147/ndt.s16664
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind comparison of ziprasidone and risperidone in the treatment of Chinese patients with acute exacerbation of schizophrenia

Abstract: Background:The aim of the study was to evaluate the efficacy and safety of ziprasidone versus risperidone in Chinese subjects with acute exacerbation of schizophrenia.Methods:In patients meeting the Chinese Classification of Mental Disorders criteria for schizophrenia and with a Positive and Negative Syndrome Scale (PANSS) total score ≥60 were randomly assigned to six weeks of double-blind treatment with ziprasidone 40–80 mg twice daily or risperidone 1–3 mg bid, flexibly dosed. Noninferiority was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…When data are reported in a categorical manner, there is evidence that almost all subjects (72–100 %) receiving oral risperidone [ 66 , 74 , 87 , 101 , 108 , 243 , 301 ] and many subjects (53–85 %) receiving risperidone long-acting intramuscular injection have HPRL [ 66 , 172 , 243 ]. The largest randomized controlled trial ( n = 555) reporting PRL data found an incidence of 73.8 % (>18 ng/ml in men, >25 ng/ml in women) in risperidone-treated subjects with first-episode psychosis [ 101 ].…”
Section: Prl and Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…When data are reported in a categorical manner, there is evidence that almost all subjects (72–100 %) receiving oral risperidone [ 66 , 74 , 87 , 101 , 108 , 243 , 301 ] and many subjects (53–85 %) receiving risperidone long-acting intramuscular injection have HPRL [ 66 , 172 , 243 ]. The largest randomized controlled trial ( n = 555) reporting PRL data found an incidence of 73.8 % (>18 ng/ml in men, >25 ng/ml in women) in risperidone-treated subjects with first-episode psychosis [ 101 ].…”
Section: Prl and Antipsychoticsmentioning
confidence: 99%
“…Most reports indicate a low incidence of PRL elevation and low to moderate levels of HPRL with ziprasidone use [ 11 , 15 , 103 , 234 , 240 , 245 , 297 , 324 326 ]. Several studies found decreased PRL levels after, respectively, 6 weeks [ 301 ], 4–8 weeks [ 90 ], 18 weeks [ 327 ], 44 weeks [ 328 ] and 1 year [ 329 ] of treatment with ziprasidone. However, ziprasidone can also be associated with HPRL.…”
Section: Prl and Antipsychoticsmentioning
confidence: 99%
“…There is a lack of highquality and large-sample-size studies of clozapine in recent years in all diagnostic groups. [190] Double-blind 38.5 [191] Double-blind [192] Double-blind [193] Double A prior study by Zipursky et al comparing weight gain dynamics from haloperidol and olanzapine (n = 263) in patients with first-episode psychosis, which is worth mentioning, showed a rapid weight increase within the first 12 weeks and a relatively stabilised situation thereafter. In the haloperidol group people gained 3.7 kg after 12 weeks, 7.1 kg after 1 year and 7.5 kg after 2 years.…”
Section: Weight Gain Due To Clozapinementioning
confidence: 99%
“…Most reports have indicated that ziprasidone use is associated with a low incidence of prolactin elevation and low to moderate levels of hyperprolactinemia [57,58,61,80,81]. Some studies revealed that treatment with ziprasidone leads to decreased prolactin levels for six weeks [82], 4-8 weeks [83], 18 weeks [84], 44 weeks [85] and one year [86], respectively. However, few trials also reported that ziprasidone induced hyperprolactinemia [87][88][89][90][91][92].…”
Section: Discussionmentioning
confidence: 99%